Day length as a key factor moderating the response of coccolithophore growth to elevated pCO 2 - Bretherton, L; Poulton, AJ; Lawson, T; Rukminasari, N; Balestreri, C; Schroeder, D; Mark Moore, C; Suggett, DJ (2019)
© 2019 The Authors. Limnology and Oceanography published by Wiley Periodicals, Inc. on behalf of Association for the Sciences of Limnology and Oceanography. The fate of coccolithophores in the future oceans remains uncertain, in part due to key factors having not been standardized across experiments. A potentially moderating role for differences in day length (photoperiod) remains largely unexplored. We therefore cultured four different geographical isolates of the species Emiliania huxleyi, as well as two additional species, Gephyrocapsa oceanica (tropical) and Coccolithus braarudii (temperate), to test for interactive effects of pCO2 with the light : dark (L : D) cycle. We confirmed a general regulatory effect of photoperiod on the pCO2 response, whereby growth and particulate inorganic carbon and particulate organic carbon (PIC : POC) ratios were reduced with elevated pCO2 under 14 : 10 h L : D, but these reductions were dampened under continuous (24 h) light. The dynamics underpinning this pattern generally differed for the temperate vs. tropical isolates. Reductions in PIC : POC with elevated pCO2 for tropical taxa were largely through reduced calcification and enhanced photosynthesis under 14 : 10 h L : D, with differences dampened under continuous light. In contrast, reduced PIC : POC for temperate strains reflected increases of photosynthesis that outpaced increases in calcification rates under 14 : 10 h L : D, with both responses again dampened under continuous light. A multivariate analysis of 35 past studies of E. huxleyi further demonstrated that differences in photoperiod account for as much as 40% (strain B11/92) to 55% (strain NZEH) of the variance in reported pCO2-induced reductions to growth but not PIC : POC. Our study thus highlights a critical role for day length in moderating the effect of ocean acidification on coccolithophore growth and consequently how this response may play out across latitudes and seasons in future oceans.